Innovation Online Learning for Islamic Education in Madrasah - Fuad, A. Jauhar; Muttaqin, Khoirul; Marpuah, Siti (Letiges, 2023)
This article discusses learning design, learning models and learning management of e-Learning-based Islamic Religious Education during the Covid-19 pandemic. This research is descriptive qualitative. The primary data source of this study was Islamic Education (PAI) teachers, and secondary data sources in this study were school profile data and Islamic Religious Education learning tools. Data collection techniques using interviews, observation and documentation. Data analysis techniques use the stages of data reduction, data presentation and conclusion. The research results are, first, the learning design of the Dick and Carrey model by carrying out ten stages. Second, the e-learning-based Islamic Education learning model is a web course, a learning process that uses the internet. The teacher goes through several stages, namely: (a) planning, (b) implementation, e-learning based Islamic Education learning is carried out in the WhatsApp class group, (c) evaluation, the teacher evaluates during the learning process through discussions and at the end of learning in the form of assignments. Third, in realizing maximum online learning, madrasas form an EFH learning management team consisting of principals, managers, editors, teachers, homeroom teachers, counsellors and parents who have their respective roles.